P568 Patients with ulcerative colitis after pouch surgery are at risk for low spinal bone mineral density: a cross sectional study. (30th January 2023) - Pfeffer-Gik, T; Godny, L; Ollech, J; Wasserberg, N; White, I; Barkan, R; Cohen, S; Avni-Biron, I; Banai, H; Snir, Y; Yanai, H; Yackobovich Gavan, M; et al.
Abstract: Background: Low bone mineral density (BMD) is prevalent in patients with inflammatory bowel diseases (IBD), specifically Crohn's disease (CD) due to multiple factors including active inflammation, use of corticosteroids, surgeries and nutritional deficiencies. Patients with ulcerative colitis (UC) who undergo total proctocolectomy and pouch surgery may develop small bowel inflammation (pouchitis) resembling CD. Data regarding their BMD are scarce. We assessed low BMD rates and risk factors in these patientsץ Methods: Patients with UC-pouch ages 18-50 without BMD assessment in the past 5 years were recruited. BMD was assessed by dual-energy x-ray absorptiometry (DEXA). Clinical data, biochemical and inflammatory markers were detected and dietary patterns were assessed using validated questionnaires. Results: Patients recruited-30: male/female 14/16; Median age 45 (IQR 31-51.7) years; median BMI 23.2 (IQR 21-26.5); median IBD duration 23 (IQR 15-30) years; median pouch age 17 (IQR 10-25) years. Low BMD detected in 16/30 (53.3%): 6/30 (20%) osteoporosis, 10/30 (33.3%) osteopenia. Low L1-L4 T-scores correlated with younger age, lower BMI and shorter disease duration (p= 0.001; p= 0.001; p= 0.023, respectively). In univariate analysis patients with low and normal BMD were comparable in age, gender, BMI, smoking, past and current medical treatment. In multivariate analysis younger age and lower BMI remained significant (age SE= 0.22, β 0.422 p=0.043, BMI SE=0.06, β=0.531 p=0.006) independently of sex, years since IBD diagnosis, and smoking. Dietary patterns were comparable (p=0.715). Conclusion: Abnormally low BMD was prevalent in over half of patients with UC-Pouch. Interestingly younger age and lower BMI were risk factors for low spinal BMD. Dietary patterns did not account for the findings. BMD should be routinely assessed in patients with UC-pouch and intervention to correct abnormally low BMD should be planned.